Age at Menarche and Risk of Multiple Sclerosis: A Prospective Cohort Study Based on the Danish National Birth Cohort. Issue 8 (25th March 2017) - Nielsen, Nete Munk; Harpsøe, Maria; Simonsen, Jacob; Stenager, Egon; Magyari, Melinda; Koch-Henriksen, Nils; Baker, Jennifer L.; Hjalgrim, Henrik; Frisch, Morten; Bager, Peter
Abstract: Few studies have addressed the possible association between age at menarche and multiple sclerosis (MS), and results are conflicting. We studied this issue in a large prospective cohort study. The study cohort comprised 77, 330 women included in the Danish National Birth Cohort (1996–2002). Information on menarcheal age was ascertained at the first interview, which took place in the 16th week of pregnancy. Women were followed for MS from the first interview to December 31, 2011. Associations between age at menarche and risk of MS were evaluated with hazard ratios and 95% confidence intervals using Cox proportional hazards regression models. Overall, 226 women developed MS during an average follow-up period of 11.7 years. Age at menarche among women with MS was generally lower than that among women without MS (Wilcoxon rank-sum test; P  = 0.002). We observed an inverse association between age at menarche and MS risk. For each 1-year increase in age at menarche, risk of MS was reduced by 13% (hazard ratio = 0.87, 95% confidence interval: 0.79, 0.96). Early age at menarche appears to be associated with an increased risk of MS. The mechanisms behind this association remain to be established.